FROM SPIRITUAL ECOLOGY TO ENVIRONMENTAL GOVERNANCE: The Ecological Engagement of Sufi Orders in Australia - Asfa Widiyanto; Fejrian Yazdajird Iwanebel; Aris Widodo (MIQOT: Jurnal Ilmu-ilmu Keislaman, 2026)
This study examines the growing significance of eco-Islamic spirituality in Australia, particularly in the post-pandemic context where environmental awareness and faith-based initiatives have gained renewed attention. The study addresses two main questions: How Sufi communities in Australia conceptualize and integrate spirituality with ecological awareness, and How they contribute to environmental protection policies and sustainability initiatives. Focusing on three Sufi orders-the Inayat Khan, the Nimatullahi, and the Ansari-this research employs qualitative field methods, including content analysis of teachings, community documents, and observations of spiritual-ecological practices, informed by Corbetta’s framework of social research. The findings indicate that these communities share a common spiritual framework for responding to ecological challenges. Their environmental engagement is grounded in Islamic ethical principles articulated by their leaders, including tauhîd (divine unity), khilâfah (stewardship), amânah (trustworthiness), mîzân (cosmic balance), Khidmah (service), and tazkiyah (spiritual transformation). These principles are translated into concrete practices such as eco-retreats, permaculture projects, waterconservation initiatives, and the use of renewable energy technologies, including solar panels. By linking spiritual teachings with practical ecological initiatives, Australian Sufi communities demonstrate how grassroots religious movements can contribute to environmental sustainability and support broader environmental governance agendas.